Co-patenting, co-ownership, and co-ideation as drivers for university business innovation: the case of public universities in Spain - Quero-Gervilla, María José; Díaz-Méndez, Montserrat; Ventura-Fernández, Rafael; Gummesson, Evert (Emerald, 2022)
Purpose: This paper explores whether, in the context of university–industry (U–I) collaboration, new innovation strategies can be developed through actors' interactions, the exchange of resources and the co-creation of value for and within the system. In the context of the U–I relationship, the innovation perspective can highlight the need to develop strategies that elicit new formulas of value co-creation, which then facilitate innovation as a result of actor collaboration. Design/methodology/approach: A total of 45 public universities in Spain, representing 95% of the total, participated in qualitative research. Personal in-depth interviews with technology transfer officers (TTOs) were conducted by an external firm; in a second phase, two of the researchers conducted eight interviews with the directors of TTOs in those universities with higher rates of transfer. Findings: Findings reveal that enterprises with a technological focus are strengthening their relationships with universities and attempting to build a university business ecosystem by designing strategies for value co-creation such as co-ownership, co-patenting, and co-invention. Research limitations/implications: The empirical research is conducted in Spain, and results should be interpreted according to this context. Future research should examine new contexts (other countries) to improve the robustness of the data and enrich the results, thus enabling generalization of the management consequences. Originality/value: The results provide a means to design strategies under a new collaborative and innovating logic. The theoretical framework contributes to theory, with implications for management.
Keywords: Innovación; Patentes; Copropiedad; Innovating; Service-dominant logic; Value co-creation; Co-patenting; Co-ownership; Co-ideation; University business ecosystem